Editorial [Hot Topic: Perspectives in Food-Based Approaches to Chronic Degenerative Diseases (Guest Editor: Alberto Battezzati)] - Battezzati, Alberto (Current Medicinal Chemistry - Immunology, Endocrine & Metabolic Agents, 2005)
For thousand of years plants provided drugs to therapists, but humans have eaten such compounds at various concentrations in common foods for even more years. It is conceivable that during evolution, phytochemicals shaped the human genoma, as bioactive substances synthesized by plants for their own purposes could produce either harmful or beneficial effects depending on human digestion, absorption and metabolism and on human ability to produce biological responses to their consumption. Now that the attention of medical research turns towards low-cost, effective and widespread approaches to contrast the pathogenic mechanisms of diseases for primary prevention, a more relevant role is warranted to foods and diet. Pharmacology classically pursues an approach of the kind “one drug-one biological target”. Foods do not work in this way: they contain an array of bioactive compounds acting on a wide range of biological function. This complexity is an true obstacle to understand how foods work in producing, modulating or preventing diseases. But the challenge is worthwhile, as by this study we can understand the role of foods in human evolutionary processes and we can produce powerful tools for human health. In order to enhance the functional quality of foods it is necessary to take into account a variety of factors that render foods different from drugs, each of whom is illustrated by one of the papers included in this hot topic. First, in general, the bioactive substances have a role in the organism producing them. In order to shape the functional profile of plants it is necessary to enhance their production of several compounds by means of genetic tools with a comprehensive knowledge of plant physiology. The review from Morandini and colleagues illustrates this concept. Second, it is different to administer the same compounds as drugs or as foods. In some cases, the composition of the diet itself, not the action of a single bioactive compound, can mimic effects produced by some drugs. The review from Bertoli and colleagues shows that the ketogenic diet determines effects similar to these of antiepileptic drugs, and that it is a valid alternative to control pharmaco-resistant seizures. Beyond the specific cases, it is thus important to take in mind that delivering bioactive compounds through foods invariably has an impact on the whole diet, and the latter factor could be equally important in producing effects on human health. Third, Tighe and colleagues describe an example of how food fortification can be successfully used to deliver components (folic acid) that are critical to prevent diseases as neural tube defects and even cardiovascular disease. However, the efficacy and safety of such approaches must be addressed in a way similar to pharmacological ones. In the case illustrated here, the importance to monitor potential adverse effects of increasing folic acid delivery is underscored, but it is definitely more difficult to perform surveillance for foods than for drugs. In her manuscript, Albertazzi gives a comprehensive review of the current process of providing clinical evidence for health effects of phytoestrogens. It is clearly pointed out that it is not sufficient to concentrate on biomarkers of disease, it is necessary to perform clinical trials and to measure clinical endpoints even when foods or food extracts are used, whose action arises from the mix of components and not from a single, pure, measurable one. Fifth, Battezzati and San Romerio show the recent developments in the understanding of chronic inflammation as a pathogenic mechanism at the root of many chronic degenerative diseases and the development of successful therapeutic and preventive strategies. Here is an example of the possibility to act on a target (inflammation) not only by means of pharmacological doses of a single drug, but by means of a number of different compounds that could act synergistically. Much work has yet to be done to achieve the target. It is exciting, however, that people from different backgrounds, plant and human genetists and physiologists, pharmacologists, physicians and epidemiologists, food scientists and nutritionists begin to converge to share knowledge and the common project to provide new foods and drugs for the increased duration of human life increasingly affected by chronic-degenerative diseases.